Supervisi Akademik Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru - Ermi Yani, Hasmi (Yayasan Sembilan Pemuda Indonesia, 2022)
Academic supervision activities are very important to be carried out in order to help improve teacher competence in managing learning activities well in order to achieve learning objectives. This article aims to examine the strategy of the head of Madrasah at MTsN 1 Prabumulih in improving teacher professionalism through academic supervision activities. This type of research is ex post facto. The results of the study indicate that academic supervision activities carried out by the Madrasah head must start from planning, implementing, and evaluating with the principles of objectivity and continuous improvement. Through this, the professionalism of teachers in schools will be easily achieved and will be able to improve the quality of learning and the quality of educational institutions.